2020
DOI: 10.7454/hubs.asia.1090320
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Use Social Networking Sites among Malaysian Chinese Older Adults

Abstract: Research has shown that social networking sites (SNS), such as Facebook and WhatsApp, make it more convenient for older adults to bond with friends and family. However, despite such benefits, studies also found few older adults use SNS, and even fewer older adults use SNS in less developed nations. Therefore, it is important to identify factors that can influence intention to use SNS in older adults, especially among the Malaysian Chinese population, as they will face an aging society earlier than other ethnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In addition to adolescent and children topics, we add an article about the elderly in this issue. Ooi, Siah, and Low (2020) illustrated the intention to use social network sites (SNS) through Technology Acceptance Model and Reasoned Action Approach on older Chinese in Malaysia. Ooi and colleagues' study found the role of subjective norm on intention to use SNS.…”
Section: A Note From Handling Editormentioning
confidence: 99%
“…In addition to adolescent and children topics, we add an article about the elderly in this issue. Ooi, Siah, and Low (2020) illustrated the intention to use social network sites (SNS) through Technology Acceptance Model and Reasoned Action Approach on older Chinese in Malaysia. Ooi and colleagues' study found the role of subjective norm on intention to use SNS.…”
Section: A Note From Handling Editormentioning
confidence: 99%